A radiomics model based on preoperative gadoxetic acid–enhanced magnetic resonance imaging for predicting post-hepatectomy liver failure in patients with hepatocellular carcinoma - Li, Changfeng; Wang, Qiang; Zou, Mengda; Cai, Ping; Li, Xuesong; Feng, Kai; Zhang, Leida; Sparrelid, Ernesto; Brismar, Torkel B.; Ma, Kuansheng (Frontiers in Oncology, 2023)
Background Posthepatectomy liver failure (PHLF) is a fatal complication after liver resection in patients with hepatocellular carcinoma (HCC). It is of clinical importance to estimate the risk of PHLF preoperatively. Aims To develop and validate a prediction model based on preoperative gadoxetic acid enhanced magnetic resonance imaging to estimate the risk of PHLF in patients with HCC. Methods 276 patients were retrospectively included and randomly divided into training and test cohorts (194:82). Clinicopathological variables were assessed to identify significant indicators for PHLF prediction. Radiomics features were extracted from the normal liver parenchyma at the hepatobiliary phase and the reproducible, robust and non-redundant ones were filtered for modelling. Prediction models were developed using clinicopathological variables (Clin-model), radiomics features (Rad-model) and their combination. Results The PHLF incidence rate was 24% in the whole cohort. The combined model, consisting of albumin-bilirubin (ALBI) score, indocyanine green retention test at 15 min (ICG-R15) and Rad-score (derived from 16 radiomics features) outperformed the Clin-model and the Rad-model. It yielded an AUC of 0.84 (95% confidence interval (CI): 0.77-0.90) in the training cohort and 0.82 (95% CI: 0.72-0.91) in the test cohort. The model demonstrated a good consistency by the Hosmer–Lemeshow test and the calibration curve. The combined model was visualized as a nomogram for estimating individual risk of PHLF. Conclusion A model combining clinicopathological risk factors and radiomics signature can be applied to identify patients with high risk of PHLF and serve as a decision aid when planning surgery treatment in patients with HCC.